Tuesday

October 21, 2014

October 21, 2014

Posted by **keisha** on Thursday, May 22, 2008 at 11:07am.

1)a(b+c)=2(-1+3)=1

2)4b^2-2ac/a+b+c= 4(-1)^2-2(2)(3)/2+-1+3

ans=-8/4=-2

- math (did i do this right) -
**Quidditch**, Thursday, May 22, 2008 at 1:49pm1. You substituted OK, but...

2(-1+3)

=2(2)

=?

2. Again, the substitution is OK, but...

4((-1)^2 - 2(2)(3)/2 + -1 + 3

=4(1) - 12/2 - 1 + 3

=4 - 6 - 1 + 3

=?

**Answer this Question**

**Related Questions**

6th grade math - Can you check these problems, please? Translate each phrase ...

6th grade math - Can you check the following problems related to inequalities? 1...

math (reiny) got an ans but would like work it pl - Given that g(x)= 2x+1/5 and ...

Math - The problem is (14ac)-a^2-2ac+b^2) I need to subtract by removing a ...

math - a straight line passing through the origin with slope m cuts the circle x...

Math - Equations of plane(check) - Consider the plane that contains points A(2,...

Math - Equations of plane(check) - Consider the plane that contains points A(2,3...

SAT Math - Can I please get some help on these questions: 1. If , find the value...

Math - complete the the table below for the fucntion y=20/x^2 for 2< or equal...

non permissable values - i have a hard time understanding the non permissable ...